Clinical characteristics of 4,520 paediatric patients infected with the SARS-CoV-2 omicron variant, in Xi'an, China - Yue, Jingwei; Cao, Jin; Liu, Lin; Yin, Li; Li, Mingyue (Frontiers in Pediatrics, 2024)
Background and objective: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has broad tissue tropism and high transmission, which are likely to perpetuate the pandemic. The study aim to analyze the clinicopathogenic characteristics in paediatric patients.In this single-centre study, we retrospectively included all confirmed cases infected by SARS-CoV-2 infection at Xi'an Children's Hospital, China, from 1 December to 31 December 2022. The demographic, clinical, laboratory, and radiological features of the patients were analysed.Results: A total of 4,520 paediatric patients with SARS-CoV-2 omicron variant infections were included. Of these, 3,861 (85.36%) were outpatients, 659 (14.64%) were hospitalised patients, and nine patients (0.20%) died. Of the nine patients who died, five were diagnosed with acute necrotising encephalopathy (ANE). The most common symptoms were fever in 4275 (94.59%) patients, cough in 1320 (29.20%) patients, convulsions in 610 (13.50%) patients, vomiting in 410 (9.07%) patients, runny nose/coryza in 277 (6.13%) patients, hoarseness of voice in 273 (6.04%) patients. A blood cell analysis showed a slight elevation of monocytes (mean: 11.140.07%). The main diagnoses for both outpatients and inpatients were respiratory infection with multisystem manifestations.A high incidence of convulsions is a typical characteristic of children infected with SARS-CoV-2. Five of the nine COVID-19 fatalities were associated with ANE. This indicates that nervous system damage in children with SARS-CoV-2 infection is more significant.